Questioning executive supremacy in an economic state of emergency. (4th May 2015) - Greene, Alan
Abstract : This paper compares and contrasts state emergency responses to national security crises with responses deployed in a period of economic crisis. Specifically, this paper challenges the appropriateness and legitimacy of the standard emergency response of legislative (as distinct from judicial) deference to the executive when confronting such economic crises. This will be done by questioning the significance in periods of economic crisis of the two principal factors that justify deferring to the executive during a state of emergency pertaining to national security: (i) the necessity of the action taken; and (ii) that the executive has an expertise in decision making in the specific area in question. Ultimately, this paper questions the application of the emergency paradigm to economic crises, arguing that such responses are rarely temporary and instead usher in a 'new normalcy'.